Câncer de mama: tendência da mortalidade no Brasil e distribuição espacial do acesso ao tratamento no estado do Paraná - Rocha-Brischiliari, Sheila Cristina (2017)
Breast cancer is the most common cancer diagnosis in women in Brazil and worldwide and is considered a major threat to public health, and should overcome heart disease as the leading cause of death in the coming years. To evaluate the impact of breast cancer mortality in Brazil, regions and Brazilian states in the period from 1996 to 2013, it was used a trend analysis. Due to the relevance of epidemiological data on breast cancer, in relation to its incidence and mortality, this issue was addressed in two studies. In the first study, it was aimed to analyze a temporal trend of general breast cancer mortality in Brazil, regions and Brazilian states. This is an exploratory, time-series study of deaths by breast cancer contained in the Mortality Information System (SIM) of women living in Brazil, regions, and Brazilian states, from 1996 to 2013. For a Trend analysis, we used the polynomial regression model, considering a significant trend that the estimated model obtained p value <0.05. There was a trend towards increased breast cancer mortality in Brazilian women (mean increase of 0.18 per year; p <0.001), with regional differences, especially those aged 20 to 49 years (0.07 per year; p < 0.001). The age group of 50 to 69 years remained constant, but with high average rates (37.14). It is noted that there is a need for more effective planning for different scenarios in the regions of Brazil in order to rethink screening strategies in relation to breast cancer mortality, especially in the younger age groups. Regarding the second study, it aimed to analyze the socioeconomic and access disparities related to breast cancer mortality in 399 cities in the State of Paraná, Brazil. It is an ecological, descriptive and analytical cross-sectional study based on secondary data from SIM, from 2009 to 2012 in the State of Paraná. Global and Local Moran analyzes were used to verify the presence of spatial autocorrelation and spatial regression model (Spatial Lag - SAR) in order to analyze the association between socioeconomic indicators, access and mortality rates for breast cancer. Significant positive spatial autocorrelation was found for breast cancer mortality rates (I = 0.5432, p = 0.001). In the spatial regression analysis, the model explained in 58% the variance of the mortality rates for breast cancer. The mortality rate due to breast cancer was negatively associated with the illiteracy rate (I = -0.0983) and positively with the access index (I = 38.469). The lower the illiteracy rate and the higher the accessibility score to cancer service the greater the specific mortality due to breast cancer in the State. These conclusions have important political implications on the organization and quality of breast cancer diagnosis and treatment services in the State of Paraná. Based on the results highlighted in the presented studies, it is concluded that there is a need for a strategic review of public health policies by the health authorities and the Ministry of Health to adopt new promotion and prevention measures for the screening and treatment of breast cancer. The first step would be to perform breast cancer screening for younger women (<50 years) and to strengthen the right of screening for women who already fit in in the process to make it more effective in all Regions. Moreover, the results suggest that these actions could be applied through different technical conducts, according to the reality of each place, region and/or State, taking into account socioeconomic and demographic factors and other risk factors, in order to guarantee that regional disparities in access to health services for diagnosis and treatment of breast cancer in a continental country can be mitigated.